2013
DOI: 10.1002/ppul.22915
|View full text |Cite
|
Sign up to set email alerts
|

Obesity negatively impacts lung function in children and adolescents

Abstract: Our results show that increasing weight status in children and adolescents is associated with a general reduction in lung volume measurements, which may reflect impaired lung function, increased respiratory symptoms, and decreased functional status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
90
3
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(106 citation statements)
references
References 39 publications
7
90
3
6
Order By: Relevance
“…, 28 All studies included in this review evaluated BMI through z-scores, which is in accordance with pediatric recommendations 2728 Of these, two studies17 , 20 showed the negative influence of BMI on FRC, ERV and RV through correlation testing and regression models. These results suggest that the higher the body composition, the lower the lung volume and capacity.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…, 28 All studies included in this review evaluated BMI through z-scores, which is in accordance with pediatric recommendations 2728 Of these, two studies17 , 20 showed the negative influence of BMI on FRC, ERV and RV through correlation testing and regression models. These results suggest that the higher the body composition, the lower the lung volume and capacity.…”
Section: Discussionmentioning
confidence: 93%
“…Thus, whereas FRC is the sum of RV and ERV, any change in these ventilatory variables implies in changes of this point of balance, as demonstrated by Davidson et al17 Changes in pulmonary bellows cause reduced lung volumes, with subsequent establishment of a restrictive pattern 2324 Kongkiattikul et al20 also reported that the reduction of FRC leads to increased air resistance, peripheral vascular resistance and impairs alveolar ventilation.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations